Polychrome glazed ware production in Tunisia during the Fatimid-Zirid period: New data on the question of the introduction of tin glazes in western Islamic lands. (December 2020) - Salinas, Elena; Reynolds, Paul; Tite, Michael S.; Pradell, Trinitat
Highlights: Continuity and innovation in the 10th CE Tunisian polychrome glazed wares. Polychrome white opaque Fatimid-Zirid glazes have quartz as opacifier. Tin glaze technology did not reach Tunisia before the Fatimid occupation of Egypt. The role of the Fatimid in the spread of tin glazes in the Mediterranean. The connection between Tunisia and Islamic Spain and Sicily. Abstract: The production of polychrome decorated ceramics began in Ifriqiya in the 9th century under Aghlabid rule, with continuity during the 10th century under the Fatimids. These comprised finely painted brown and green designs with a characteristic yellow background (a transparent lead glaze containing iron oxide). This production was substituted in the 11th century by a polychrome production over a white tin opaque glaze. The hypothesis stating that tin glazes were introduced in Tunisia after the Fatimids took over Egypt has been recently proposed. However, polychrome ceramics with a white opaque background have been found in 10th century archaeological sites which might indicate otherwise. A ceramic assemblage found at the site of Bir Ftouha dating from the Fatimid-Zirid period which contains polychrome with both transparent yellow and white opaque backgrounds has been analysed. The white opaque glazes do not contain tin but were opacified by the addition of large quartz particles. This study supports the theory that tin glazes reached Tunisia after the Fatimid occupation of Egypt and is the first step to answering many open questions regarding the spread of tin glaze in the Mediterranean, the role of the Fatimids and the connections of Ifriqiya with Islamic Spain and Sicily.